Effect of Pulmonary Rehabilitation on Dyspnoea, Functional Capacity and Thoracic Excursion in Chronic Obstructive Pulmonary Disease: A Case Report - Priyanka K Chilhate; Lajwanti Lalwani (Adwani) (Journal of Clinical and Diagnostic Research)
Chronic Obstructive Pulmonary Disease (COPD) is a top cause of death. It is a lung disease that gets worse over time and includes emphysema and chronic bronchitis, causing blocked airflow. Hospitalisations, mortality and exacerbations of COPD are all increased by poor air quality. Significant occupational dosages include excessive pesticide exposure and home air pollution from burning coal, wood, animal dung and crop residues. Besides medical treatments, pulmonary rehabilitation is crucial for patient recovery from hospital to home. This study focuses on a 67-year-old man who visited a respiratory clinic with breathing problems for the past 15 days and chest pain for the past week. He also had a yellowish cough and occasional fever in the last week. With a 5-year history of COPD, he used an inhaler twice daily. His symptoms worsened in winter but stayed the same throughout the day. A chest X-ray confirmed a flare-up of COPD. A two-week pulmonary rehab plan with physical therapy was recommended. Before starting treatment, a baseline assessment was done, including measures like Modified Medical Research Council (mMRC) grading for breathlessness, 6-Minute Walk Distance (6MWD) and chest movement. Following the completion of the instructed pulmonary rehabilitation, significant improvements in dyspnoea grading, 6MWD, and thoracic were found. The findings imply that when modified to each patient’s specific requirements and capabilities, an organised pulmonary rehabilitation program can have an important beneficial therapeutic impact on those suffering from Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD).